2019
DOI: 10.1186/s13054-019-2621-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased β-Lactams dosing regimens improve clinical outcome in critically ill patients with augmented renal clearance treated for a first episode of hospital or ventilator-acquired pneumonia: a before and after study

Abstract: BackgroundAugmented renal clearance (ARC) is recognized as a leading cause of β-lactam subexposure when conventional dosing regimens are used. The main objective was to compare the clinical outcome of ARC patients treated by conventional or increased β-lactam dosing regimens for a first episode of hospital or ventilator-acquired pneumonia (HAP-VAP).MethodsIn this single-center, retrospective study, every ARC patient treated by β-lactam for a first episode of HAP-VAP was included during two 15-month periods, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 33 publications
2
39
0
1
Order By: Relevance
“…In view of the fact that target attainment is observed in only about 60-65% of critically ill patients receiving antibiotics and considering the increasing resistance to antibiotics worldwide, higher dosing in these patients could be an alternative strategy to obtain better target attainment when TDM is not available. Carrie et al showed that, in critically ill patients with ARC, higher than licensed dosing regimens of beta-lactam antibiotics may be safe and effective in reducing the rate of therapeutic failure [47]. Moreover, Imani et al found that prescribed daily antibiotic dose ≥ 1.5 times the product information recommendations was associated with better target attainment [26].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the fact that target attainment is observed in only about 60-65% of critically ill patients receiving antibiotics and considering the increasing resistance to antibiotics worldwide, higher dosing in these patients could be an alternative strategy to obtain better target attainment when TDM is not available. Carrie et al showed that, in critically ill patients with ARC, higher than licensed dosing regimens of beta-lactam antibiotics may be safe and effective in reducing the rate of therapeutic failure [47]. Moreover, Imani et al found that prescribed daily antibiotic dose ≥ 1.5 times the product information recommendations was associated with better target attainment [26].…”
Section: Discussionmentioning
confidence: 99%
“…The difference is mainly attributable to the different definitions of ARC and possible differences in patient selection, such as the inclusion or exclusion of patients with renal impairment. 6 Among patients undergoing neurosurgery, the incidence of ARC varies by disease, complications, the time course of treatment, and other factors. Considering the relatively high incidence of ARC, it might influence the pharmacokinetics of drugs, especially those excreted through the kidneys such as vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Renal hyperfiltration is now increasingly being recognized as a clinical entity ( 16 18 ). A highly relevant clinical consequence is the augmented clearance of renally excreted drugs, most notably antibiotics, which is important for daily practice as well as for clinical trials investigating novel therapeutic compounds ( 19 21 ). Adjustment of the dosing of these drugs should be considered when GFR is increased, as is already common practice when the GFR is decreased ( 22 ).…”
Section: Discussionmentioning
confidence: 99%